A Raf-like MAPKKK gene, GhRaf19, negatively regulates tolerance to drought and salt and positively regulates resistance to cold stress by modulating reactive oxygen species in cotton. (November 2016) - Jia, Haihong; Hao, Lili; Guo, Xulei; Liu, Shuchang; Yan, Yan; Guo, Xingqi
Highlights: GhRaf19 -silencing enhanced tolerance to drought and salt by modulating ROS. GhRaf19 -silenced attenuated cold resistance with ROS accumulation. GhRaf19- overexpression in N. benthamiana reduced tolerance to drought and salt. GhRaf19- overexpression in N. benthamiana increased resistance to cold stress. Abstract: Mitogen-activated protein kinase kinase kinases (MAPKKKs) function at the top level of MAPK cascades and play important roles in plant development and stress responses. Although MAPKKKs comprise the largest family in the MAPK cascades, very few Raf-like MAPKKKs have been functionally identified, especially in the economically important crop cotton. In this study, a Raf-like MAPKKK gene, GhRaf19, was characterized for the first time in cotton. Our data show that the expression of GhRaf19 was inhibited by PEG and NaCl and induced by cold (4 °C) and H2 O2 . Furthermore, when GhRaf19 was silenced in cotton using virus-induced gene silencing (VIGS), tolerance to drought and salt stress were enhanced, the accumulation of reactive oxygen species (ROS) was reduced, and ROS-related gene expression was increased. Consistent with these results, in N. benthamiana, overexpressing- GhRaf19 reduced tolerance to drought and salt. However, GhRaf19 -silenced plants showed lowered resistance to cold in cotton, and this effect was correlated with the accumulation of ROS. In contrast, overexpressing GhRaf19 in N. benthamiana increased resistance to cold by inducing higher levels of expression and activity of ROS-related antioxidant genes/enzymes. These results indicate that GhRaf19 negatively regulates tolerance to drought and salt and positively regulates resistance to cold stress by modulating cellular ROS in cotton.